Analisis Tulisan Teks Eksplanasi Peserta Didik Kelas V Melalui Model Pembelajaran Multiliterasi - Nisa Hamidah; Dian Indihadi; Erwin Rahayu Saputra (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to describe the results of the activity of analyzing written explanatory texts through the implementation of a multiliteracy learning model for fifth grade students at SDN 3 Banjarwangi. The analysis reviewed is in terms of aspects of writing explanatory text skills. As for the skills of writing explanatory texts, there are three aspects that are the focus of analysis, namely content aspects, text structure aspects, and linguistic aspects. In this study, the method used is descriptive analysis method. The research data source is in the form of explanatory text of fifth grade students as a result of the implementation of the multiliteracy learning model. Data collection techniques in this study were carried out through test techniques (assignments) and documentation. The data analysis technique was carried out through three stages, namely the verification, tabulation, and assessment stages. Based on the research findings of 15 students, it was shown that the students’ writing explanatory texts obtained results in categories ranging from pretty good, good, and very good.